The Effects of Acute Aerobic Exercise on Blood Pressure, Arterial Function, and Heart Rate Variability in Men Living With HIV - Barros, Juliana Pereira; de Paula, Tainah; Mediano, Mauro Felippe Felix; Rangel, Marcus Vinicius dos Santos; Monteiro, Walace; Cunha, Felipe Amorim da; Farinatti, Paulo; Borges, Juliana Pereira (Frontiers in Physiology, 2021)
Purpose This study aims to investigate the effects of acute cycling on blood pressure (BP), arterial function, and heart rate variability (HRV) in men living with HIV (MLHIV) using combined antiretroviral therapy (cART). Methods Twelve MLHIV (48.7 ± 9.2 years; 25.2 ± 2.8 kg m–2) and 13 healthy controls (41.2 ± 9.9 years; 26.3 ± 2.9 kg m–2) performed a cycling bout (ES) (intensity: 50% oxygen uptake reserve; duration: time to achieve 150 kcal—MLHIV: 24.1 ± 5.5 vs. controls: 23.1 ± 3.0 min; p = 0.45), and a 20-min non-exercise session (NES). Results At rest (p < 0.05), MLHIV presented higher brachial systolic/diastolic BP (SBP/DBP: 123.2 ± 14.2/76.8 ± 6.3 vs. 114.3 ± 5.1/71.6 ± 2.6 mmHg) and central BP (cSBP/cDBP: 108.3 ± 9.3/76.5 ± 6.5 vs. 101.6 ± 4.9/71.3 ± 4.4 mmHg) vs. controls but lower absolute maximal oxygen uptake (2.1 ± 0.5 vs. 2.5 ± 0.3 L min–1) and HRV indices reflecting overall/vagal modulation (SDNN: 24.8 ± 7.1 vs. 42.9 ± 21.3 ms; rMSSD: 20.5 ± 8.5 vs. 38.1 ± 22.8 ms; pNN50: 3.6 ± 4.2 vs. 13.6 ± 11.3%). DBP postexercise lowered in controls vs. MLHIV (∼4 mmHg, p < 0.001; ES: 0.6). Moreover, controls vs. MLHIV had greater reductions (p < 0.05) in augmentation index (−13.6 ± 13.7 vs. −3.1 ± 7.2% min–1; ES: 2.4), and HRV indices up to 5 min (rMSSD: −111.8 ± 32.1 vs. −75.9 ± 22.2 ms min–1; ES: 3.8; pNN50: −76.3 ± 28.3 vs. −19.0 ± 13.7% min–1; ES: 4.4). Within-group (ES vs. NES; p < 0.05) reductions occurred in controls for SBP (∼10 mmHg, 2 h), DBP (∼6 mmHg, 20, 30, and 70 min), cSBP (∼9 mmHg, 30 min), cDBP (∼7 mmHg, 30 and 70 min), augmentation index (∼10%, 30 min), and pNN50 (∼20%; up to 2 h), while in MLHIV only cSBP (∼6 mmHg, 70 min) and cDBP (∼4 mmHg, 30 min) decreased. Similar increases (up to 5 min) in heart rate (∼22 bpm) and decreases in SDNN (∼18 ms) and rMSSD (∼20 ms) occurred in both groups. Conclusion MLHIV under cART exhibited attenuated postexercise hypotension vs. healthy controls, which seemed to relate with impairments in vascular function.